BUDGET ALLOCATION AND UTILIZATION IN LOCAL SCHOOLS IN THE PHILIPPINES - Beronibla, Ma. Robeca Mae B. (IDEAS: Journal of Management & Technology, 2024)
The study aimed to determine the extent of budget allocation and the degree of budget utilization of schools in a province in the Philippines. The descriptive-correlational design was utilized to treat the data from the 175 employees composed of School Heads, Senior Bookkeepers and Disbursing Officers of Secondary Schools as respondents. This study was descriptive because it described the extent of budget allocation and the degree of budget utilization of schools. Likewise, it was correlational as it also tried to find out whether there was a significant difference in the extent of budget allocation when grouped according to their school location and school size; and whether there was a significant difference in the degree of budget utilization when grouped according to their school location and school size. Moreover, it was also correlational as it tried to measure whether there was indeed a significant relationship between the extent of budget allocation and the degree of budget utilization among the respondents. The results revealed that the extent of budget allocation was high. In terms of fixed costs, it was high and in terms of variable costs, it was average; and the degree of budget utilization as a whole and in terms of procurement and augmentation was high.  The results also showed that there was a significant difference in the extent of budget allocation and the degree of budget utilization when respondents are grouped according to their school size. Finally, the extent of budget allocation and the degree of budget utilization of schools in the Province of Capiz are significantly related and mutually dependent. The findings indicate an alignment of budgetary priorities with actual spending, highlighting a strategic approach to resource allocation. The significant relationship underscores the importance of coherent and targeted budgeting practices, contributing to efficient utilization of financial resources. Considering the study’s findings, it is recommended to implement a transparent and collaborative budgeting process, involving key stakeholders such as parents, teachers, and other partners. Moreover, to effectively track the utilization of funds, it is recommended to establish a reliable monitoring system of budget utilization. Lastly, to maintain transparency and accountability in the allocation and utilization of budgets, it is recommended regular audits be conducted regularly.